The Current State of Integrating Reading Comprehension and Linguistic Skills in Mother Tongue Education: Based on a Teacher Survey - Navruzova Xosiyat Izzatullo qizi (Researchparks Publishing, 2026)
This article analyzes the current state of the integration of reading comprehension and linguistic skills in mother tongue education, based on a teacher survey. It examines the role of linguistic knowledge in the process of reading comprehension, the possibilities of teaching language units in connection with the text's content, and the views of mother tongue teachers regarding existing methodological needs. The survey results indicate that teachers recognize the importance of units such as the contextual meaning of a word, inter-sentential connections, pronouns, conjunctions, and particles in the process of reading comprehension. At the same time, the findings substantiate the need for specialized tasks and methodological recommendations aimed at the integrated development of reading comprehension and linguistic skills.